1992
DOI: 10.2307/1591531
|View full text |Cite
|
Sign up to set email alerts
|

Avian Paramyxovirus Type 1 Infections in Racing Pigeons in California. I. Clinical Signs, Pathology, and Serology

Abstract: An outbreak of diarrhea and neurological disease in California racing pigeons caused by avian paramyxovirus type 1 (PMV-1) is documented. Predominant clinical signs were polydipsia, ataxia, poor balance, torticollis, head tremors, inability to fly, and diarrhea that was unresponsive to therapy. Gross pathologic findings were often unremarkable or non-specific. The predominant histologic lesions were interstitial nephritis, chronic tubular necrosis, lymphoplasmacytic infiltration within the kidney, liver, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
8
21
0
Order By: Relevance
“…Like most authors reporting experimental pPMV-1 infections (Barton et al, 1992;Johnston & Key, 1992;Lumeij & Stam, 1985;Maeda et al, 1987), we did not observe gross pathological changes, although Pearson et al (1987) noticed haemorrhages on digestive organs and on pancreas, and El Mubarak et al (1990) observed haemorrhages also on the brain.…”
Section: Discussionsupporting
confidence: 77%
“…Like most authors reporting experimental pPMV-1 infections (Barton et al, 1992;Johnston & Key, 1992;Lumeij & Stam, 1985;Maeda et al, 1987), we did not observe gross pathological changes, although Pearson et al (1987) noticed haemorrhages on digestive organs and on pancreas, and El Mubarak et al (1990) observed haemorrhages also on the brain.…”
Section: Discussionsupporting
confidence: 77%
“…Pancreatitis occurs in several avian viral diseases (Randall and Reece, 1996) and specifically in chickens and pigeons due to PMV-1 infection (Barton et al, 1992;Meulemans et al, 1998). To our knowledge this is the first time pancreatitis has been reported in houbara bustards asso-ciated with PMV-1 and septicemic avipox virus infections.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, greenish white diarrhoea and nervous signs were more frequently observed. Barton et al (1992) also observed dirrhoea and nervous signs associated with ND in racing pigeons. In the present study nervous signs in 27.59% cases, diarrhoea in 48.28% and shivering in 24.14% cases were observed but Fischer (1986) observed nervous signs in 86% cases, diarrhoea in 18% and paralysis of legs and wings in 9% of naturally affected pigeons.…”
Section: Discussionmentioning
confidence: 75%